Determining the optimal duration of the COVID-19 suppression policy: A cost-benefit analysis - Anna Scherbina (American Enterprise Institute (AEI), 2020)
Without any intervention, the novel coronavirus would cost the U.S. economy over 9 trillion.
Keywords: A; 330; COVID-19; Pandemic Curve; Attack Rate; Cost-Benefit Analysis; Non-Pharmaceutical Interventions; Public Health Policy; Suppression; Mitigation; Lockdown